Emergency and critical care providers' perception about the use of bedside ultrasound for confirmation of above-diaphragm central venous catheter placement. Issue 1 (January 2020) - Tran, Quincy K.; Foster, Mark; Bowler, Justin; Lancaster, Mia; Tchai, Jennifer; Andersen, Katie; Matta, Ann; Haase, Daniel J.
Abstract: Introduction: Chest radiography (CXR) is commonly used to confirm the proper placement of above-diaphragm central venous catheters (CVCs) and to detect associated complications. Recent studies have shown that point-of-care ultrasound (POCUS) has better sensitivity and is faster than CXR for these purposes. We were interested in documenting how often emergency medicine and critical care practitioners perform POCUS to confirm proper CVC positioning as well as their confidence in performing it. Methods: We surveyed members of our state's chapters of the College of Emergency Physicians and the Society of Critical Care Medicine between April and December 2018. Our primary outcome was the percentage of providers who would agree to perform only POCUS, forgoing CXR, for confirmation of CVC position. We performed multivariable logistic regressions to measure associations between demographic, clinical information, and outcomes. Results: One hundred thirty-six providers participated (a 25% participation rate). Their specialties were as follows: emergency medicine, 75%; critical care, 13%; and emergency medicine/critical care, 11%. Thirty-one percent would use POCUS only for CVC confirmation, while 42% were confident in performing POCUS for this purpose. Multivariable logistic regressions showed that performing more non-procedural ultrasound examinations was associated with a higher likelihood of agreeing to perform POCUS only (OR, 2.9; 95% CI: 1.3–6.3). Forty-six percent of relevant comments suggested more training to increase the use of POCUS. Conclusion: Participants in this study did not frequently use POCUS for CVC confirmation. Designers of training curricula should consider including more instruction in the use of POCUS to confirm proper CVC placement and to detect complications. Abstract : Health profession; Medicine; Emergency medicine; Medical imaging; Central venous catheters; Above diaphragm; POCUS; Barriers